Obesity and Economic Performance of Young Workers in Italy - Giovanni S. F. Bruno; Floro Ernesto Caroleo; Orietta Dessy (Institute for the Study of Labor (IZA), 2015)
In this paper we explore recent ISFOL-PLUS 2006-2008-2010 data available for Italy about height and weight of young workers with the purpose of analysing the relationship between measures of obesity and measures of economic performance. Among the latter, we introduce job satisfaction, both overall and for nine specific aspects, which has not been previously considered in the literature on the effects of obesity. Interestingly enough, we find that BMI does not discriminate young workers with respect to their job earnings, but it does affect negatively young workers' job satisfaction with important gender effects.
Keywords: J28; J81; I14; 330; obesity; overweight; body mass index; job satisfaction; gross income